Abortion in Review of the Fatwa of the Indonesian Ulema Council (MUI) - Rizani, Akhmad Kamil; Pelu, Ibnu Elmi A.S; Darojat, Much Hasan (FENOMENA, 2024)
Abortion as a practice of termination of pregnancy is not a foreign concept in our society. Abortion is a controversial issue because it is related to religion and health issues. The opinions of scholars of the fiqh madhhabs on abortion differ. Over twenty-two years, the Indonesian Ulema Council has made decisions on abortion. This shows that there are pretty complex issues in the practice of abortion. This research is a literature review that is descriptive-analytic. This literature research uses written sources, such as books and various other literature related to the reasoning of the MUI fatwa on abortion. The result of this research is that MUI uses the tarjih method in collecting and identifying the opinions of the scholars of mazhab in determining fatwa related to abortion.